Chemical Evolution of Nitrogen-based Compounds in Mozzarella Cheeses - Barone, Caterina (Chemistry of Foods,, 2018)
This Brief evaluates the consequences of protein modifications in cheeses, with special emphasis on mozzarella cheeses. It explains the influence of biogenic amines on food quality and safety. As certain biogenic amines display a toxic potential to humans, considerable research has been undertaken in recent years to evaluate their presence in fermented foods, such as cheeses. This Brief summarizes how the presence of amines is influenced by different factors such as cheese variety, seasoning and microflora. The authors compare typical profiles of different products, e.g. ripe vs. unripe cheeses, focusing also on the different types of mozzarella cheeses. The Brief also introduces several analytical methods and simulation techniques, which are being used to evaluate the evolutive profiles of different selected molecules, protein aggregation, or proteolysis. .